Foreign Ownership and the Enforcement of Corporate Governance Reforms - Bibek Bhatta; Andrew P. Marshall; Suman Neupane-Joshi; Chandra Thapa (Queen's University Belfast, Queen's Management School, 2021)
This study examines whether a stronger corporate governance enforcement regime influences the investment decisions of foreign portfolio investors in an emerging market context. Using a natural experiment provided by an Indian corporate governance regulatory reform introduced in 2000, but for which stricter sanctions for non-compliance were imposed in 2004 our results provide strong evidence that governance reforms that include stricter sanctions for non-compliance lead to higher foreign ownership. In the context of prevalence of weak enforcement (of existing regulations) in emerging markets, this study provides empirical support to the notion that strictly enforcing the existing governance regulations has the potential to attract higher level of foreign investment. The results suggest that policy measures aimed at attracting foreign investors in emerging markets should not only concentrate on adopting the best international corporate governance practices but should also signal strong enforcement of these regulations by assigning significant penalties for non-compliance
Keywords: 330